Effects of warm-up on blood gases, lactate and acid-base status during sprint swimming - Robergs, R. A.; Costill, D. A.; Fink, W. J.; Williams, C.; Pascoe, D. D.; Chwalbinska-Moneta, J.; Davis, J. A. (International Journal of Sports Medicine, 1990)
Warm-up reduced the disturbance in blood acid-base balance during the swimming exercise. Warm-up was found to be beneficial and not a hindrance to performance. Warm-up swimming can be used for reasons other than performance improvements (e.g., environmental familiarization, injury prevention, psychological focusing, neuromuscular facilitation). If it produces additional physiological benefits then its justification is even further supported.